1980
DOI: 10.1111/j.1471-4159.1980.tb03687.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Prolyl Endopeptidase During Maturation of Rat Brain and Hydrolysis of Substance P by the Purified Enzyme

Abstract: We determined changes in prolyl endopeptidase activity in developing rat brain. A new and highly sensitive fluorogenic substrate, 7-(succinyl-Gly-Pro)-4-methylcoumarinamide, was used for determination of the enzyme activity. The enzyme activity per brain increased until 2 weeks of age, and then decreased during maturation. The enzyme was purified about 7800-fold from the brain of the rat at 2 or 3 weeks of age. The enzyme has a pH optimum of 5.8 to 6.5, and an approximate molecular weight of 70,000. The enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(40 citation statements)
references
References 16 publications
1
39
0
Order By: Relevance
“…(2)(3)(4)(5), al though its physiological role still remains obscure. Since vasopressin, among these peptides, has been suggested to be deeply involved in the process of learning and memory in animal experiments (6-9), Yoshimoto et al synthesized a variety of PED inhibitors and demon strated a probable relationship between their PED in hibition in vitro and anti-amnesic activity in vivo (10).…”
mentioning
confidence: 99%
“…(2)(3)(4)(5), al though its physiological role still remains obscure. Since vasopressin, among these peptides, has been suggested to be deeply involved in the process of learning and memory in animal experiments (6-9), Yoshimoto et al synthesized a variety of PED inhibitors and demon strated a probable relationship between their PED in hibition in vitro and anti-amnesic activity in vivo (10).…”
mentioning
confidence: 99%
“…Previous studies have shown abundant fluctuation of enzyme activity and expression of POP during brain development [5,26,27]. High POP activities were measured particularly during early brain ontogeny.…”
Section: Introductionmentioning
confidence: 99%
“…18) In addition, bacterial (Flavobacterium) and mammalian (bovine brain) enzyme genes were cloned and their amino acid sequences had 48% identity 24) ; we therefore investigated the inhibitory activities of six compounds by two different assays. One is the method of Yoshimoto et al, 9) which is the most popular Flavobacterium PEP inhibition assay, and the other is the method of Kato et al, 19) which measures inhibitory activity against PEP from rat brain supernatant. The concentrations of these compounds causing 50% inhibition are shown in Table 2, together with the positive controls, EGCG and Z-Pro-prolinal.…”
Section: Resultsmentioning
confidence: 99%
“…PEP Inhibition Assay (Rat Brain Supernatant) PEP activity was measured by a modification of the method of Kato et al 19) In brief, the brain of a rat was homogenized in 3 volumes of 0.1 M phosphate buffer (pH 7.0). After centrifugation at 10000ϫg for 20 min, the supernatant was used for the enzyme assay.…”
Section: Generalmentioning
confidence: 99%